Regulation of hematopoietic stem cells differentiation, self-renewal, and quiescence through the mTOR signaling pathway - Ling, Bai; Xu, Yunyang; Qian, Siyuan; Xiang, Ze; Xuan, Shihai; Wu, Jian (Frontiers in Cell and Developmental Biology, 2023)
Hematopoietic stem cells (HSCs) are important for the hematopoietic system because they can self-renew to increase their number and differentiate into all the blood cells. At a steady state, most of the HSCs remain in quiescence to preserve their capacities and protect themselves from damage and exhaustive stress. However, when there are some emergencies, HSCs are activated to start their self-renewal and differentiation. The mTOR signaling pathway has been shown as an important signaling pathway that can regulate the differentiation, self-renewal, and quiescence of HSCs, and many types of molecules can regulate HSCs’ these three potentials by influencing the mTOR signaling pathway. Here we review how mTOR signaling pathway regulates HSCs’ three potentials, and introduce some molecules that can work as the regulator of HSCs’ these potentials through the mTOR signaling. Finally, we outline the clinical significance of studying the regulation of HSCs’ three potentials through the mTOR signaling pathway and make some predictions.